2003
DOI: 10.1074/jbc.m306216200
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Orthologue of Mammalian Puromycin-sensitive Aminopeptidase Has Roles in Embryogenesis and Reproduction

Abstract: Peptide hydrolysis was inhibited by the metal-chelating agent 1,10-phenanthroline and by the aminopeptidase inhibitors actinonin, amastatin, and leuhistin. However, the enzyme was ϳ100-fold less sensitive toward puromycin (IC 50 , 135 M) than other PSA homologues. Following inactivation of the enzyme, aminopeptidase activity was recovered with Zn 2؉ , Co 2؉ , and Ni 2؉ . Silencing expression of pam-1 by RNA interference resulted in 30% embryonic lethality. Surviving adult hermaphrodites deposited large numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 62 publications
(60 reference statements)
1
41
0
Order By: Relevance
“…In Arabidopsis, the single PSA homolog is essential for meiosis (Sanchez-Moran et al, 2004). Less is known about C. elegans PSA, although a previous study showed that PAM-1 is expressed in intestinal cells and in neurons of the head, and in the male tail (Brooks et al, 2003). However, this study did not address maternal, paternal or early embryonic expression, due to germline silencing of the transgene reporter (Brooks et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In Arabidopsis, the single PSA homolog is essential for meiosis (Sanchez-Moran et al, 2004). Less is known about C. elegans PSA, although a previous study showed that PAM-1 is expressed in intestinal cells and in neurons of the head, and in the male tail (Brooks et al, 2003). However, this study did not address maternal, paternal or early embryonic expression, due to germline silencing of the transgene reporter (Brooks et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
“…Less is known about C. elegans PSA, although a previous study showed that PAM-1 is expressed in intestinal cells and in neurons of the head, and in the male tail (Brooks et al, 2003). However, this study did not address maternal, paternal or early embryonic expression, due to germline silencing of the transgene reporter (Brooks et al, 2003). The aminopeptidase activity of C. elegans PAM-1 is similar to other PSA molecules, except that it is less sensitive to puromycin (Brooks et al, 2003).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations